|February 11th, 2017, 10:48 PM||#1|
Joined: Feb 2017
From: Bay Area, US
Math Focus: 3x+1
Summing a set past the end of the set.
The sum from n=1 to k+d of a_n is equal to a_k.
We can deduce that a_n = a_(n-d) - a_(n-d-1) and if a_1 = 1 and d = 1 it results in:
When we change the value of d, it becomes more chaotic. When d=4, we get:
Some of you who are keen may notice Pascal's triangle hidden in there, and in fact, when d approaches infinity, it will give us alternating numbers in pascal's triangle, separated by infinite zeros.
But these are trivial.
The sum from n=1 to dk of b_n is equal to b_k.
We set d=2
the first 4 are [1,0,x,y] where x+y=-1, so there are infinitely many routes we could go. The simplest being x=-1, y=0
so, the first 6 are [1,0,-1,0,x',y'] where x'+y'=-1, using the same logic,
the first 8 are [1,0,-1,0,-1,0,x'',y''] where x''+y''=0, using x''=y''=0
... using the simplest solution
we get [1,0,-1,0,-1,0,0,0,-1,0,1,0,0,0,0,0,0,0,-1,0,1,0,1,0,0,0,0,0,0,0,...] Most likely never getting a digit above 1, due to y*=0 and b_n - b_(n+1)<=1
When we add the rule that x*=y* it might be different but I'm much too tired to pay any attention.
As a final note, I apologize if this is already a thing and I'm taking credit for it, if it is, I'd like to learn more.
Last edited by skipjack; February 12th, 2017 at 02:54 AM.
|end, past, set, summing|
|Thread||Thread Starter||Forum||Replies||Last Post|
|Trying to create formula for dividing and summing numbers||oleoleole||Elementary Math||3||June 11th, 2016 09:31 AM|
|Deriving the formula for summing a sequence of squares||Mr Davis 97||Pre-Calculus||11||August 17th, 2014 09:05 AM|
|Looking at past posts||wrightarya||New Users||0||July 18th, 2014 04:07 AM|
|summing a finite exponential series||UncleFester||Real Analysis||2||December 30th, 2013 06:03 AM|
|Summing Divergent Series||mathbalarka||Number Theory||16||November 24th, 2013 09:01 AM|